The Bias and Uncertainty of Redundant and Sky-based Calibration Under Realistic Sky and Telescope Conditions - Joseph, R.; Trott, Cathryn; Wayth, Randall (Institute of Physics Publishing, 2018)
The advent of a new generation of low frequency interferometers has opened a direct window into the Epoch of Reionisation (EoR). However, key to a detection of the faint 21-cm signal, and reaching the sensitivity limits of these arrays, is a detailed understanding of the instruments and their calibration. In this work we use simulations to investigate the bias and uncertainty of redundancy based calibration. Specifically, we study the influence of the flux distribution of the radio sky and the impact of antenna position offsets on the complex calibration solutions. We find that the position offsets introduce a bias into the phase component of the calibration solutions. This phase bias increases with the distance between bright radio sources and the pointing center, and with the flux density of these sources. This is potentially problematic for redundant calibration on MWA observations of EoR fields 1 and 2. EoR field 0, however, lacks such sources. We also compared the simulations with theoretical estimates for the bias and uncertainty in sky model based calibration on incomplete sky models for the redundant antenna tiles in the MWA. Our results indicate that redundant calibration outperforms sky based calibration due to the high positional precision of the MWA antenna tiles.